THE APPLICATION OF PLACENTA CRYOEXTRACT IN COMPLEX TREATMENT OF PATIENTS WITH PHLEGMONS OF MAXILLOFACIAL LOCALIZATION - V.O. Lichman; K.P. Lokes; D.S. Avetikov; M.G. Skikevich; V.V. Bondarenko; R.A. Prykhidko (Український стоматологічний альманах, 2020)
Today the problem of pathogenesis and rational treatment of purulent-inflammatory odontogenic diseases of the maxillofacial area is quite relevant in the field of medical and SOCIAL problems. In recent years, the number of patients with odontogenic inflammatory does not catch an illness, while the number of complications increases. In case of the development of purulent inflammation the complex of interrelated morphological, biochemical, immunological and other changes is observded. The basis in the complex treatment of phlegmon of the maxillofacial area and neck of any localization is active surgical treatment. General therapy for odontogenic inflammatory diseases of the maxillofacial area primarily provides control of infection and intoxication, aimed at normalization of the impaired functions of organs and systems.